Retrospective evaluation of the correlation between somatostatin receptor PET/CT and histopathology in patients with suspected intracranial meningiomas - Ebner, Ricarda Katharina Viktoria; Braach, Jana; Rübenthaler, Johannes; Cyran, Clemens C.; Sheikh, Gabriel T.; Brendel, Mattias; Albert, Nathalie L.; Tiling, Reinhold; Greve, Tobias; Hinterberger, Anna; Fabritius, Matthias P.; Fink, Nicola; et al. (Journal of nuclear medicine, 2025)
The aim of this retrospective study was to evaluate the correlation between findings from somatostatin receptor (SSTR) PET/CT and histopathology in patients with suspected intracranial meningiomas. Methods: We conducted a retrospective analysis of 8,077 SSTR imaging studies recorded in our institutional database between 2006 and 2021. In total, 223 SSTR PET/CT scans were performed for suspected meningioma, and 240 lesions were matched with histopathology results within 4 mo. Reports from SSTR PET/CT scans and histopathology were retrospectively reviewed to assess the presence of intracranial meningiomas. The positive and negative predictive values, sensitivity, specificity, and overall diagnostic accuracy of SSTR PET/CT were calculated. The SUVmax, SUVmean, and SUVpeak were determined for each lesion. Results: In 222 (92.5%) of 240 lesions, meningioma was accurately identified by SSTR PET/CT and confirmed by histopathology. In 7 cases (2.9%), SSTR PET/CT suspected meningioma was not confirmed by histopathology (false-positive). Furthermore, in 11 cases (5%), meningioma was neither suspected by SSTR PET/CT nor confirmed by histopathology (true-negative result). There were no false-negative findings in our cohort. SSTR PET/CT demonstrated a sensitivity of 100% (95% CI, 98.4%-100%) and a specificity of 61.1% (95% CI, 35.8%-82.7%) in detecting meningiomas. Positive predictive value was 96.9% (95% CI, 93.8%-98.8%), and negative predictive value was 100% (95% CI, 71.5%-100%). The overall diagnostic accuracy was 97.1%. The receiver-operating-characteristic analysis for SUVmax in predicting histopathology results showed an area under the curve of 94%, indicating an excellent ability of SUVmax to distinguish between positive and negative histopathologic findings. Conclusion: SSTR PET/CT is a precise imaging modality for detecting intracranial meningiomas, as demonstrated by its high sensitivity. However, in 2.9% of cases, despite a positive PET/CT result, histopathology did not confirm the presence of a meningioma. Integration of MRI, histopathology, and SSTR PET/CT supports informed treatment decisions.